Behavioral, Biochemical, and Molecular Indices of Stress are Enhanced in Female Versus Male Rats Experiencing Nicotine Withdrawal - TORRES, OSCAR V.; GENTIL, LUCIANA G.; NATIVIDAD, LUIS A.; Carcoba, Luis M.; ODELL, LAURA E. (Frontiers in Psychiatry, 2013)
Stress is a major factor that promotes tobacco use and relapse during withdrawal. Although women are more vulnerable to tobacco use than men, the manner in which stress contributes to tobacco use in women versus men is unclear. Thus, the goal of this study was to compare behavioral and biological indices of stress in male and female rats during nicotine withdrawal. Since the effects of nicotine withdrawal are age-dependent, this study also included adolescent rats. An initial study was conducted to provide comparable nicotine doses across age and sex during nicotine exposure and withdrawal. Rats received sham surgery or an osmotic pump that delivered nicotine. After 14 days of nicotine, the pumps were removed and controls received a sham surgery. Twenty-four hours later, anxiety-like behavior and plasma corticosterone were assessed. The nucleus accumbens (NAcc), amygdala, and hypothalamus were examined for changes in corticotropin-releasing factor (CRF) gene expression. In order to differentiate the effects of nicotine withdrawal from exposure to nicotine, a cohort of rats did not have their pumps removed. The major finding is that during nicotine withdrawal, adult females display higher levels of anxiety-like behavior, plasma corticosterone, and CRF mRNA expression in the NAcc relative to adult males. However, during nicotine exposure, adult males exhibited higher levels of corticosterone and CRF mRNA in the amygdala relative to females. Adolescents displayed less nicotine withdrawal than adults. Moreover, adolescent males displayed an increase in anxiety-like behavior and an up-regulation of CRF mRNA in the amygdala during nicotine exposure and withdrawal. These findings are likely related to stress produced by the high doses of nicotine that were administered to adolescents to produce equivalent levels of cotinine as adults. In conclusion, these findings suggest that intense stress produced by nicotine withdrawal may contribute to tobacco use in women.